The Use of Technology Acceptance Model to Evaluate MSME Perspectives on E-Payment System - Cahyani, Ayudhea; Yeskainayah, Annasa; Hamdah, Lailatul; Suryaatmaja, Kevin (International Journal Labs, 2023)
Background: Payment system changes in transaction patterns need to be followed by business actors to survive and develop in facing the New Normal era. It is important for Micro, Small, Medium Enterprises (MSMEs) to be able to adapt and transform by utilizing digital technology. Considering to Indonesia's large number of e-payment users, MSME players are heavily utilizing the payment option to construct a more effective and efficient payment system. However, not all MSME’s owner have the intention about using digital payments. This causes economic lagging, due to the shift in social transaction behavior from the physical economy to the virtual economy. Aim: The research would like to measure the use of technology acceptance model to evaluate MSME perspectives on e-payment system. Method: Concurrent mixed methodology, which is an analytical technique used in this study that integrates or affiliates qualitative and quantitative forms by providing a variety of sources of evidence, quantitative and qualitative data combined can contribute to enhancing the validity and reliability of the research findings. It can help to reduce the risk of bias or error that may arise from using only one method. As an outcome, we want to provide a thorough overview of the research problem. The population is MSMEs registered with Asosiasi Gula Rafinasi Indonesia (AGRI) of 980 MSMEs. With a target sample of 90 SMEs. Findings: The results of the Jaccard’s coefficient test show that all the variables tested have an influence on the MSME intends to use electronic payments as a way to make purchases.